PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPAS KELAS IV SDN 106162 MEDAN ESTATE T.A 2025/2026 - Yuni Siregar; Nurmayani; Nurhairani; Apiek Gandamana; Syahrial (STKIP Subang, 2025)
The study was conducted to determine the effect of the pair check cooperative learning model on the learning outcomes of fourth-grade students at SDN 106162 Medan Estate in the subject of IPAS (Science and Technology) with the material of buying and selling activities as one of the fulfillment of needs. This study used a quasi-experimental method with a nonequivalent control group design. The research population consisted of 72 students, namely all fourth-grade students at SDN 106162 Medan Estate, which consisted of two classes, namely class IV A with 34 students and class IV B with 38 students. Class IV A was the control class that was given treatment using the conventional learning model, and class IV B was the experimental class that was given treatment using the pair check cooperative learning model. The instrument used was a cognitive test in the form of 25 multiple-choice questions. Based on the results of processing the data from the independent sample t-test using SPSS 31, the results of this study showed that the learning outcomes of students using the pair check cooperative learning model were higher than those of students using the conventional learning model. The independent sample t-test showed a two-sided p < 0.05, namely 0.001 < 0.05, meaning that H0 was rejected and Ha was accepted. Thus, it can be concluded that the use of the pair check cooperative learning model can significantly affect student learning outcomes.